Bubble-induced Color Doppler Feedback for Histotripsy Tissue Fractionation - Miller, Ryan M. (IEEE Trans Ultrason Ferroelectr Freq Control, 2016)
Histotripsy therapy produces cavitating bubble clouds to increasingly fractionate and eventually liquefy tissue using high intensity ultrasound pulses. Following cavitation generated by each pulse, coherent motion of the cavitation residual nuclei can be detected using metrics formed from ultrasound color Doppler acquisitions. In this paper, three experiments were performed to investigate the characteristics of this motion as real-time feedback on histotripsy tissue fractionation. In the first experiment, bubble-induced color Doppler (BCD) and particle image velocimetry (PIV) analysis monitored the residual cavitation nuclei in the treatment region in an agarose tissue phantom treated with 2-cycle histotripsy pulses at > 30 MPa using a 500 kHz transducer. Both BCD and PIV results showed brief chaotic motion of the residual nuclei followed by coherent motion first moving away from the transducer and then rebounding back. Velocity measurements from both PIV and BCD agreed well, showing a monotonic increase in rebound time up to a saturation point for increased therapy dose. In a second experiment, a thin layer of red blood cells (RBC) was added to the phantom to allow quantification of the fractionation of the RBC layer to compare with BCD metrics. A strong linear correlation was observed between the fractionation level and the time to BCD peak rebound velocity over histotripsy treatment. Finally, the correlation between BCD feedback and histotripsy tissue fractionation was validated in ex vivo porcine liver evaluated histologically. BCD metrics showed strong linear correlation with fractionation progression, suggesting that BCD provides useful quantitative real-time feedback on histotripsy treatment progression.